The Clinical Outcome of UK Military Personnel Who Received a Massive Transfusion in Afghanistan During 2009. Issue Volume 157:Issue (2011)Supplement 4 (1st December 2011) - Allcock, Edward; Woolley, T; Doughty, H; Midwinter, M; Mahoney, PF; Mackenzie, I
Abstract : Objectives: The UK Defence Medical Services has developed a Massive Transfusion Protocol (MTP) that forms part of the initial Damage Control Resuscitation process for severely injured combat casualties. The key objectives of this retrospective review of MTP recipients are to document the survival rates, level of critical care support required and the blood components transfused as part of the Massive Transfusion Protocol in Afghanistan during 2009. In addition to providing a measure of our current effectiveness it should also provide a reference point for future reviews as the MTP continues to evolve. Methods: This was a collaborative project involving the Royal Centre for Defence Medicine and the Critical Care Department, University Hospitals Birmingham. It was limited to UK military personnel who were injured in 2009 and received massive transfusions (defined as the transfusion of 10 or more units of packed red blood cells over a 24-hour period) at Camp Bastion Role 3 Medical Facility, Afghanistan. Results: During the 12-month period, 59 personnel received massive transfusions. 51 (86%) personnel survived to be discharged from hospital in the UK. 48 (92%) personnel required ventilatory support for a median of 3 (2-8) days. The longest period of ventilation was 40 days; 29 (55%) personnel required vasopressor support and eight personnel (15%) required renal replacement therapy. The median total transfusion of blood components was 45 (28.5-62) units. There were seven transfusions of more than 100 units. Five of the personnel in this group (including the recipient of a 237-unit transfusion) survived to be discharged from University Hospitals Birmingham. On average, 1.21 (SD 0.28) units of packed red blood cells were transfused for every unit of fresh frozen plasma. Conclusions: The use of the current MTP was associated with a high rate of survival. Survivors require a continuity of critical care with a median demand for 3 days. The early use of plasma and platelets can be successfully delivered in the battlefield despite operational and logistic constraints.